(untitled) (Research, Society and Development, 2022)
Amidst the social, political and economic transformations of a globalized world, the conception of higher education is in constant questioning. In recent years, as a result of new market demands, new undergraduate courses have emerged and others have been adapted. Traditional courses face challenge of keeping up with these changes. Among them, the Bachelor of Law courses stand out. Considering the need overcome of the traditional paradigm of positivism, the research aims to analyze the commitment of Law professors to the paradigm shift in legal education, through the encouragement of students to reflexivity and creativity. Of an empirical nature, this research is characterized as a descriptive-analytical study and developed, according to the use of the results, in a pure way with a descriptive approach and qualitative data analysis. An investigation was carried out with the faculty (n=10) of a Bachelor’s Degree in Law at a private Higher Education Institution in Fortaleza/CE. For data collection, a questionnaire was formulated based on an instrument constructed by Eunice Maria Lima Soriano de Alencar, in 1995, to assess the degree of encouragement to different aspects of creativity by university professors. Among the main results found, it is highlighted that the teachers, even though they believe to encourage the students’ reflexivity and creativity, adopt traditional methodologies, centered on the absorption of contents, with little diversified teaching methods and learning assessment reduced to measuring the absorption of the content taught in the classroom or form textbooks.